Balloon-Occluded Trans-Arterial Chemoembolization Technique with Alternate Infusion of Cisplatin and Gelatin Slurry for Small Hepatocellular Carcinoma Nodules Adjacent to the Glisson Sheath. (9th May 2019) - Irie, Toshiyuki; Takahashi, Nobuyuki; Kamoshida, Toshiro
Abstract : Objective. It is difficult to control small hepatocellular carcinoma (HCC) nodules adjacent to the Glisson sheath (GS) by trans-arterial chemoembolization (TACE) probably due to multiple small tumor feeders directly branching from the trunk artery. The purpose of this study was to conduct a retrospective evaluation of a new TACE technique called the repeated alternate infusion of cisplatin solution and gelatin slurry distal to balloon occlusion (RAIB-TACE), for the treatment of small HCC nodules adjacent to GS. Materials and Methods. Small nodules less than 4 cm attached to proximal portion of the subsegmental to lobar level portal branch were retrospectively selected. Between January 2011 and April 2014, 29 nodules in 29 patients were treated by super-selective lipiodol TACE/balloon-occluded TACE (B-TACE) (Lip-TACE group). Since April 2014, treatment protocols for small nodules adjacent to GS were changed, and 14 nodules in 12 patients were treated by RAIB-TACE (RAIB-TACE group). In RAIB-TACE group, alternate infusion of cisplatin solution and sparse gelatin slurry (mixture of 80 mg of gelatin fragments and 20 mL of contrast medium) were repeated until arterial flow was ceased. In Lip-TACE group, lipiodol was used as drug carrier and dense gelatin slurry (mixture of 80 mg of gelatin fragments and 2 mL of contrast medium) as embolization material. Dynamic CT/MRI was obtained 1-3 months after TACE, and response of each nodule was evaluated basing on modified RECIST criteria. Results. In RAIB-TACE group, all 14 nodules (100%) were diagnosed as CR or PR. In Lip-TACE group, 18 of 29 (62.1%) were diagnosed as CR or PR. There was a statistically significant difference in objective response ratio between the groups (p=0.008, Fisher's test). Biloma (n=1) and benign stricture of the right hepatic duct (n=1) were seen in RAIB-TACE group. The biloma shrunk without treatment and the patient had no symptom, but the patient with biliary stricture repeated cholangitis and was treated by administration of antibiotics. Conclusion. The study results show that RAIB-TACE is more effective than lipiodol TACE/B-TACE for small hepatocellular carcinoma adjacent to GS. We speculate that one of the reasons to explain why Lip-TACE is inferior to RAIB-TACE is that viscous lipiodol or dense gelatin slurry could not flow into small tumor feeders effectively.